Coletivo de Estudos e Ações Indígenas (CEAI): da resistência à afirmação - A Coleção Retomadas - Souza, Diogo Bandeira de (Universidade Federal de São Carlos, 2024)
This research aims at studying resistance and affirmation movements developed by Coletivo de Estudos e Ações Indígenas (CEAI), linked to an extension course at Department of Letters at Universidade Estadual de Ponta Grossa/Paraná (UEPG). I highlight that among these movements, the Retomadas Collection will be my main source of analysis and reflections, as it corresponds to the affirmation of the indigenous people who study at the aforementioned educational institution. However, I warn that the Retomadas Collection, as well as the CEAI, are composed of UEPG students only, nor only by indigenous people. However, the works in the Retomadas Collection are exclusively written by indigenous people and I dedicate an entire chapter of the thesis to them, as they materialize, in my opinion, the decolonial struggle at the university, giving new meaning to the canonical concept of episteme, as well as allowing the university an alternative of alternatives. As a theoretical-methodological reference, I bring the epistemologies of the South, with Boaventura de Sousa Santos as the main name, as well as the other authors from the decolonial perspective, with emphasis on the indigenous researchers at CEAI.
Colectivo de Estudios y Acciones Indígenas (CEAI): de la resistencia a la afirmación - La Colección Retomadas
Keywords: Epistemologias do Sul; Descolonização; Saberes Indígenas; Coletivo de Estudos e Ações Indígenas; Decolonization; Epistemologies South; Knowledge Indigenous; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO